The use of force military power and international politics - Art, Robert J.; Greenhill, Kelly M. (Rowman & Littlefield Publishers, Inc., 2015)
This book brings together enduring, influential works on the role of military power in foreign policy and international politics. Now in its eighth edition, this fully updated reader has been significantly revised with twenty innovative and up-to-date selections meticulously chosen and edited by leading scholars Robert Art and Kelly Greenhill.